Determinants of Tourist Attraction of the Heritage Tourism - KAHARUDDIN, KAHARUDDIN; NAPITUPULU, Junika; JULIANA, JULIANA; PRAMONO, Rudy; SARAGIH, Elza Leyli Lisnora (Journal of Environmental Management and Tourism, 2021)
Heritage tourism is a journey where the purpose of the trip is to see or witness heritage ceremonies and enriches, strengthen faith. The research result on the effect of Tourist’s motivation on tourist decision to heritage tourism in Dairi, it was discovered that there is an increase in the effect of tourist's motivation on tourist decision to heritage tourism in Dairi. Based on this research regarding the effect of service quality on tourist decision to heritage tourism in Dairi, it was discovered that there is an effect of service quality on tourist decision on heritage tourism in Dairi. With the improvement of Service Quality, tourist decision to heritage tourism in Dairi can be increased. Based on the findings of this research, it was discovered that tourist satisfaction has no effect on tourist decision to heritage tourism in Dairi. The decreased Tourist Satisfaction leads to a decline in tourist’s decision. With regard to the effect of the tourist’s motivation, service quality, and Tourist satisfaction on tourist decision to heritage tourism in Dairi, it was revealed that these three variables (Tourist’s Motivation, Service Quality, and Tourist Satisfaction) have simultaneous effects on tourist decision to heritage tourism in Dairi.